2016
DOI: 10.1016/j.neuroscience.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

GABA-A receptor activity in the noradrenergic locus coeruleus drives trigeminal neuropathic pain in the rat; contribution of NAα1 receptors in the medial prefrontal cortex

Abstract: Trigeminal neuropathic pain is described as constant excruciating facial pain. The study goal was to investigate the role of nucleus locus coeruleus (LC) in a model of chronic orofacial neuropathic pain (CCI-ION). The study examines LC's relationship to both the medullary dorsal horn receiving trigeminal nerve sensory innervation and the medial prefrontal cortex (mPFC). LC is a major source of CNS noradrenaline (NA) and a primary nucleus involved in pain modulation. Although descending inhibition of acute pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 70 publications
5
50
2
Order By: Relevance
“…The locus coeruleus (LC), containing by far the greatest number of noradrenergic neurons in the brain, could be described by many as a “pain suppressor.” We refer the reader to excellent comprehensive overviews of the basic science that describes the contribution of the LC to the inhibition of acute and chronic pain (Pertovaara, ; Llorca‐Torralba et al, ). By contrast, the current review argues that, after traumatic nerve injury, the LC is not an inhibitor but instead becomes a chronic neuropathic “pain generator.” In support of this opposing position, we emphasize two of our own studies, using standard models of neuropathic pain following traumatic injury to the sciatic or trigeminal nerves (Brightwell and Taylor, ; Kaushal et al, ), as well as several others. This topic is interesting given our stance that facilitation increases over time after nerve injury, and the lack of knowledge surrounding the underlying mechanisms that cause the transition from acute to chronic pain.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The locus coeruleus (LC), containing by far the greatest number of noradrenergic neurons in the brain, could be described by many as a “pain suppressor.” We refer the reader to excellent comprehensive overviews of the basic science that describes the contribution of the LC to the inhibition of acute and chronic pain (Pertovaara, ; Llorca‐Torralba et al, ). By contrast, the current review argues that, after traumatic nerve injury, the LC is not an inhibitor but instead becomes a chronic neuropathic “pain generator.” In support of this opposing position, we emphasize two of our own studies, using standard models of neuropathic pain following traumatic injury to the sciatic or trigeminal nerves (Brightwell and Taylor, ; Kaushal et al, ), as well as several others. This topic is interesting given our stance that facilitation increases over time after nerve injury, and the lack of knowledge surrounding the underlying mechanisms that cause the transition from acute to chronic pain.…”
Section: Introductionmentioning
confidence: 88%
“…Similarly, intracerebroventricular administration of anti‐DβH‐saporin but not control IgG‐saporin, given 3 weeks after CCI‐ION surgery, reduced behavioral signs of mechanical hypersensitivity for at least 1 month after initiation of treatment (Kaushal et al, ). Taken together, these data indicate that the LC facilitates both the development and maintenance of neuropathic pain following injury to the sciatic or trigeminal nerves (Brightwell and Taylor, ; Kaushal et al, ).…”
Section: Noradrenergic Projections From the Lc Facilitate Neuropathicmentioning
confidence: 98%
See 1 more Smart Citation
“…In normal conditions, the noradrenergic system primarily functions to inhibit nociceptive transmission. Following nerve injury, the plastic changes that occur shift the inhibitory tone of the noradrenergic system to facilitate nociceptive transmission instead (Brightwell and Taylor, 2009;Kaushal et al, 2016). Therefore, the increase in expression of a 2A -adrenoceptor following CCI in vehicle-treated group may be due to plastic changes that occur, abolishing the inhibitory tone of the noradrenergic system.…”
Section: Chia Et Almentioning
confidence: 99%
“…Accumulating evidence has indicated that GABA A -mediated activation of neurons facilitates hypersensitivity in the central nervous system (CNS) [11]. Study has shown the up-regulation of GABA A α4 subunit is associated with anxiety disorders in the female rat [12].…”
Section: Introductionmentioning
confidence: 99%